2022
DOI: 10.1111/ijpo.12915
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of scaling up a whole‐of‐community intervention: The Romp & Chomp early childhood obesity prevention intervention

Abstract: Summary Background Given the high prevalence of early childhood overweight and obesity, more evidence is required to better understand the cost‐effectiveness of community‐wide interventions targeting obesity prevention in children aged 0–5 years. Objectives To assess the cost‐effectiveness of the Romp & Chomp community‐wide early childhood obesity prevention intervention if delivered across Australia in 2018 from a funder perspective, against a no‐intervention comparator. Methods Intervention costs were estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(43 citation statements)
references
References 29 publications
0
43
0
Order By: Relevance
“…It is also noteworthy that effective resource management can also have a significant impact on the sustainability of obesity-prevention efforts [ 77 ]. For instance, there is substantial evidence that availability of finances and effective management of such resources can single-handedly determine the longevity and scalability of most obesity-prevention efforts [ 78 ]. Accordingly, there is increasing interest by contemporary interventionists regarding novel, cost-effective strategies in implementing WSAs to obesity prevention.…”
Section: Discussionmentioning
confidence: 99%
“…It is also noteworthy that effective resource management can also have a significant impact on the sustainability of obesity-prevention efforts [ 77 ]. For instance, there is substantial evidence that availability of finances and effective management of such resources can single-handedly determine the longevity and scalability of most obesity-prevention efforts [ 78 ]. Accordingly, there is increasing interest by contemporary interventionists regarding novel, cost-effective strategies in implementing WSAs to obesity prevention.…”
Section: Discussionmentioning
confidence: 99%
“…Four further studies 24,[30][31][32] were identified through the grey literature search, resulting in a total of 17 studies included in this review. 17,18,24,[30][31][32][33][34][35][36][37][38][39][40][41][42][43] From the 17 included studies, 15 discrete economic evaluations, protocols, or costing studies of 13 CBIs were identified (Table 1). The economic evaluation of a CBI was reported in full in the publication by Ananthapavan et al 34 and also included as part of a larger prioritysetting study.…”
Section: Study Inclusionmentioning
confidence: 99%
“…Twelve CBIs were conducted exclusively in high-income countries (HICs) (Table 1). 17,18,24,[30][31][32][33][34][35][36][37][38][39]42,43 The OPIC study was conducted in both high-income and upper-middle-income countries from the Western Pacific region (Fiji, Tonga, New Zealand, Australia). 40,41 Six CBIs were implemented in Australia (BAEW, Fun 'n Healthy in Moreland!, hypothetical CBI, Obesity Prevention and Lifestyle [OPAL],…”
Section: Summary Of Intervention Characteristicsmentioning
confidence: 99%
See 2 more Smart Citations